(untitled) (Semiárida, 2025)
Urban green spaces provide important contributions to sustainability. In Argentina, exotic plants have traditionally been used for landscaping, to the detriment of native species. The Neighborhood Commission of Irala and Adyacencias was created in 1999 and formalized in 2002 as a non-profit Civil Association, aiming to improve the quality of life in the City of Buenos Aires, propose neighborhood improvement projects, and promote citizen participation, with all initiatives collective incidence. In the neighborhood of La Boca, there was a large railway property that was gradually assigned to different uses. In 2000, the Commission requested its conversion into green spaces, based on the need for permeable surfaces, forested areas, public spaces, and greater urban connectivity. When a real estate project was announced for the site, the Commission turned to the City Ombudsman’s Office and decided to submit a Popular Initiative bill. The proposal established that the park should consist of native species to restore the original vegetation. A total of 17,271 signatures were collected, and in 2003, an agreement was signed between the National and City governments to allocate the land for public and community use. After learning about the Participatory Landscape Diagnosis Program, the Commission chose to manage the project using this approach. In 2004, the law for rezoning the land was passed. In 2006, the park was inaugurated, becoming the first Public Park in La Boca, the first in the city composed of native flora, and designed through a participatory process. This achievement later inspired the creation of other native flora parks in the city, enhancing biodiversity and promoting citizen involvement in the pursuit of a more sustainable and equitable city.